Traitement biologique des eaux usées par L’Azolla et son incorporation dans l’alimentation des volailles cas de Fayoumi (Mostaganem). - Benessalah, Batoul; Hadjeba, chaimaa (My University, 2023)
This research presents a comprehensive study on the use of azolla in wastewater treatment. The results are remarkable, showing an impressive treatment rate of 85% for biochemical oxygen demand (BOD5), 72.87% for chemical oxygen demand (COD), and a significant reduction of 96.63% in suspended solids (SS). Moreover, the use of wastewater led to a significant increase in the protein content of azolla, reaching up to 27%. To deepen this research, different concentrations of azolla from wastewater were integrated into chicken feed, specifically 5%, 10%, and 15%, in parallel with similar concentrations of azolla grown in separate batches. The results of this experiment were simply exceptional, particularly in terms of the nutritional quality of the meat and the weight gain of Fayoumi hens. Notably, the concentration of 15% azolla from wastewater yielded highly significant results. It is important to mention that even azolla from wastewater was used as a dietary supplement up to 50% with standard feed. This approach also produced splendid results in terms of lipid content and weight gain.
Keywords: Azolla; wastewater; Fayoumi; treatment; protein; meat; feed